2005
DOI: 10.1124/jpet.105.084517
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Naphthalene Bioactivation and Nasal Airflow Cause Region-Specific Injury Patterns in the Nasal Mucosa of Rats Exposed to Naphthalene by Inhalation

Abstract: Despite the fact that naphthalene (NA), a volatile, ubiquitous air pollutant, was recently identified as a probable human carcinogen, little is known about nasal cytotoxicity from inhaled NA. To define and compare acute nasal injury from inhalation and systemic NA exposures, male Sprague-Dawley rats were exposed to filtered air; 3.4 or 23.8 ppm NA by inhalation for 4 h; or to 0, 25, 50, 100, or 200 mg/kg NA via intraperitoneal injection. Severe cellular injury occurred exclusively in the olfactory mucosa 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
20
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 21 publications
5
20
0
Order By: Relevance
“…This observation agrees with those of Lee et al (2005), who observed cellular necrosis exclusively in the olfactory mucosa of Sprague-Dawley rats exposed to 3.4 ppm or 24.8 ppm NA for 4 h. Lee et al (2005) observed that activity of CYP450 in the olfactory region of the rat nasal cavity was significantly greater than in the non-olfactory regions supporting the concept that NA metabolism is a contributing factor of acute NA toxicity. Because the nasal respiratory epithelium does have CYP450 activity (Bogdanffy, 1990;Lee et al, 2005), this may explain why low NA concentrations (≥ 1 ppm) for long periods (≥ 90 days) produce minimal hyperplasia. A combination of concentration, uptake (Morris & Buckpitt, 2009), airflow distribution (Kimbell et al, 1997), and metabolism are all likely factors contributing to regional dosimetry of NA in the nasal cavity.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…This observation agrees with those of Lee et al (2005), who observed cellular necrosis exclusively in the olfactory mucosa of Sprague-Dawley rats exposed to 3.4 ppm or 24.8 ppm NA for 4 h. Lee et al (2005) observed that activity of CYP450 in the olfactory region of the rat nasal cavity was significantly greater than in the non-olfactory regions supporting the concept that NA metabolism is a contributing factor of acute NA toxicity. Because the nasal respiratory epithelium does have CYP450 activity (Bogdanffy, 1990;Lee et al, 2005), this may explain why low NA concentrations (≥ 1 ppm) for long periods (≥ 90 days) produce minimal hyperplasia. A combination of concentration, uptake (Morris & Buckpitt, 2009), airflow distribution (Kimbell et al, 1997), and metabolism are all likely factors contributing to regional dosimetry of NA in the nasal cavity.…”
supporting
confidence: 90%
“…Interestingly, minimal degeneration and/or necrosis of olfactory epithelium was observed in F344 rats following only a single 6-h exposure of 1 ppm NA, but higher concentrations of NA (≥ 10 ppm) were needed to produce necrosis in respiratory epithelium following acute exposure (Dodd et al, 2010). This observation agrees with those of Lee et al (2005), who observed cellular necrosis exclusively in the olfactory mucosa of Sprague-Dawley rats exposed to 3.4 ppm or 24.8 ppm NA for 4 h. Lee et al (2005) observed that activity of CYP450 in the olfactory region of the rat nasal cavity was significantly greater than in the non-olfactory regions supporting the concept that NA metabolism is a contributing factor of acute NA toxicity. Because the nasal respiratory epithelium does have CYP450 activity (Bogdanffy, 1990;Lee et al, 2005), this may explain why low NA concentrations (≥ 1 ppm) for long periods (≥ 90 days) produce minimal hyperplasia.…”
supporting
confidence: 89%
“…NTP reports may be found by Report number at http://ntp.niehs.nih.gov/go/14374 rior squamous epithelium and are active upon direct contact with the NM when administered by inhalation (Feron et al, 2001), such as formaldehyde, are not detailed in this review, although inhalation is an important route of human exposure and many volatile carcinogens act directly on the NM. Also, some chemicals that are cytotoxic to the NM by the inhalation route produce similar effects when delivered systemically (Keller et al, 1997;Lee et al, 2005). Nevertheless, here we focus on organic chemicals that have cytotoxic and carcinogenic activity in the NM upon systemic distribution following oral or perenteral administration.…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to degenerative cellular changes in Bowman's gland or due to a secretion of intraepithelial mucosubstances in the mucous cells of these glands. A similar response has been observed after exposure to the mechanistically related cytotoxicant, naphthalene (32). OE has the highest levels of P450 s in nasal mucosa, primarily located to sustentacular cells and the to acinus area of Bowman's glands (9), and lesions to this epithelial type thus correspond well with the putative mechanism of toxicity.…”
Section: Discussionmentioning
confidence: 53%